Un modelo explicativo de la conducta hacia la enfermedad mental - Sarah García (Salud Pública de México, 2002)
Objective. To evaluate a theoretical model designed toexplain behaviors toward mental illness, considering somevariables related to the construct. Material and Methods.A survey was conducted in 1996 on mental disorder beliefs,attitudes, and behavioral intentions. The sample populationwas stratified by socioeconomic status, age, and gender. Studysubjects were 800 individuals from Mexico City?s generalpopulation. A data collection instrument was constructedand validated, consisting of 120 Likert-type items with fiveoptions each. Data were coded and analyzed with the softwarepackage SPSS. Internal consistency of the scales wasassessed using Cronbach?s alpha and construct validity withfactorial analysis. Student?s t test and ANOVA were used tocompare the groups in the different strata. Results. Themodel allowed to confirm the predictive capacity of thecausal chain connecting beliefs, attitudes, and intentions;nevertheless, other study variables did not contribute toexplain it, and behavior was scarcely influenced by intentions,depending mainly on experimented necessity. Conclusions.Study findings constitute a basis to understandthe attitudes of shame and fear usually related to mentalillnesses, to plan efficient actions aimed at modifying them,and to design programs to promote mental health. The Englishversion of this paper is available at: http://www.insp.mx/salud/index.html